Management of conflict injuries to the upper limb. Part 1: assessment and early surgical care. (July 2022) - Brown, Kate V.; Roberts, Darren C.; Wordsworth, Matthew; Duraku, Liron S.; Jose, Rajive M.; Power, Dominic M.; Stapley, Sarah A.
Upper limb injuries are common in conflict zones. The functions of the upper limb are impossible to replicate with prosthetic replacement and wherever possible attempts should be made to preserve the limb with further secondary reconstruction aimed at restoration of function. Casualty assessment, haemorrhage control and resuscitation are simultaneously undertaken at the receiving medical facility. Primary surgical management involves decontamination and debridement, skeletal stabilization, restoration of vascularity, compartment fasciotomy where indicated and wound temporization with dressings. Operative findings and interventions should be documented and if evacuation of the casualty is possible, copies should be provided in the medical records to facilitate communication in the chain of care. Secondary procedures are required for further assessment and debridement prior to planning reconstruction and definitive fracture stabilization, nerve repair, wound cover or closure.